Laboratory Manual for Practical Botany - Kuruppuarachchi, K.A.J.M. (Nawala: OUSL, 2018)
basic laboratary tools and techniques, identifications of macro-molecules, practical skills in plant diversity & microbiology
Keywords: microbiology, plant diversity, macro-molecules